Physical Properties of LaxSc1-xSb Alloys: FPLMTO Approach - Mohamed Ghezali (Research Aspects in Chemical and Materials Sciences Vol. 6, 2023)
We calculated the structural, electronic and optical properties of the LaxSc1-xSb ternary alloy with 0 \(\) x \(\) 1 by using the first-principles full potential linear muffin-tin orbital (FPLMTO) method based on the generalized gradient approximation (GGA96). The lattice constants, bulk modulus, electronic band structure, density of states, and optical properties such as dielectric function, refractive index, and extinction coefficient for (x=0.25, 0.5, and 0.75) are calculated and discussed. Our results are in good agreement with available data in the literature. It is observed that for x=0.75, the compound is characterized by the direct band gap materials approximately zero between M and \(Γ\) direction. It has been found that the La0.75Sc0.25Sb system is probably a semiconductor despite that both binary (LaSb) and (ScSb) are metals in the rocksalt phase. The density of states calculations indicates that the lower part of the conduction b and is totally occupied by Sc-3d and La-4f states and the upper part of the conduction band is occupied by the La-5d state while the lower part of the valence band is dominated by the Sb-5p state.